Electro-optical imaging system performance / Gerald C. Holst. - Holst, Gerald C. (SPIE monograph, 2017)
This sixth edition emphasizes staring array analysis and provides: NVIPM, TRM4, and TOD comparisons, frequency (MTF) versus spatial (pixels on target) analysis, two-dimensional versus two-directional analyses, FA/d approach to modeling and system resolution, in-band and out-of-band sampling artifacts, numerous trade studies. Copublished with JCD Publishing.